Characterization of viral diversity in wild marmot blood from the Qinghai–Tibet Plateau - Wu, Haisheng; Jiang, Xiaojie; Xi, Yuan; Ning, Songyi; Wu, Hailian; Xin, Wenyuan; Peng, Wenxuan; Wang, Shengjun; Zhang, Wen (Frontiers in Microbiology, 2026)
IntroductionThis study aimed to characterize the viral diversity in the blood of marmots in the Qinghai-Tibet Plateau region, to assess their role as potential viral reservoirs and evaluate the potential implications for wildlife and human health.MethodologySeventy marmot blood samples were collected from Yushu and Guoluo Prefectures in Qinghai Province. Viral communities were comprehensively analyzed using high-throughput sequencing and bioinformatics techniques.ResultsAnalysis identified a wide range of viral families, including Anelloviridae, Flaviviridae, Parvoviridae, and Polyomaviridae, and revealed multiple novel viral sequences. Notably, we documented the first evidence of Anelloviridae in marmot serum; phylogenetic analysis indicated these sequences cluster with those from marmot feces and tissues, suggesting a natural host relationship. A critical finding was the detection of Tick-borne encephalitis virus, with a sequence highly similar to human-derived strains, implying potential involvement of marmots in the transmission cycle. Furthermore, identification of a novel polyomavirus was supported by prediction of all main large tumor antigen functional domains and motifs, including a putative nuclear localization signal between its LXCXE motif and origin-binding domain, typical of mammalian-infecting polyomaviruses. Comparative analysis revealed significant regional differences in viral diversity between sampling areas, potentially linked to local ecological factors.DiscussionThis study significantly expands the known viral diversity in marmots and underscores their role as potential zoonotic reservoirs. However, the functional and pathogenic implications of these viruses require further experimental validation. These findings highlight the importance of ongoing wildlife surveillance for understanding viral ecology and mitigating emerging public health risks.